Myeloperoxidase Deficiency Alters the Process of the Regulated Cell Death of Polymorphonuclear Neutrophils - Kremserová, Silvie; Kocurková, Anna; Chorvátová, Michaela; Klinke, Anna; Kubala, Lukáš (Frontiers in Immunology, 2022)
Polymorphonuclear neutrophils (PMNs) play a key role in host defense. However, their massive accumulation at the site of inflammation can delay regenerative healing processes and can initiate pathological inflammatory processes. Thus, the efficient clearance of PMNs mediated by the induction of regulated cell death is a key process preventing the development of these pathological conditions. Myeloperoxidase (MPO), a highly abundant enzyme in PMN granules, primarily connected with PMN defense machinery, is suggested to play a role in PMN-regulated cell death. However, the contribution of MPO to the mechanisms of PMN cell death remains incompletely characterized. Herein, the process of the cell death of mouse PMNs induced by three different stimuli – phorbol 12-myristate 13-acetate (PMA), opsonized streptococcus (OST), and N-formyl-met-leu-phe (fMLP) – was investigated. MPO-deficient PMNs revealed a significantly decreased rate of cell death characterized by phosphatidylserine surface exposure and cell membrane permeabilization. An inhibitor of MPO activity, 4-aminobenzoic acid hydrazide, did not exhibit a significant effect on PMA-induced cell death compared to MPO deficiency. Interestingly, only the limited activation of markers related to apoptotic cell death was observed (e.g. caspase 8 activation, Bax expression) and they mostly did not correspond to phosphatidylserine surface exposure. Furthermore, a marker characterizing autophagy, cleavage of LC3 protein, as well as histone H3 citrullination and its surface expression was observed. Collectively, the data show the ability of MPO to modulate the life span of PMNs primarily through the potentiation of cell membrane permeabilization and phosphatidylserine surface exposure.